Effects of Cu, K, and Guanidinium Addition to CH3NH3PbI3 Perovskite Solar Cells - Ayu Enomoto; Atsushi Suzuki; Takeo Oku; Masanobu Okita; Sakiko Fukunishi; Tomoharu Tachikawa; Tomoya Hasegawa (Chemistry Proceedings, 2022)
Fabrication and characterization of CH3NH3PbI3 perovskite solar cell with the addition of copper (Cu2+), and potassium (K) or guanidinium (GA) was performed. The additive effects on the photovoltaic properties, morphologies, and crystalline structures were investigated by the experimental results, electronic structures, and thermodynamic stabilities. The stability and conversion efficiency of the perovskite solar cells was improved by incorporating Cu2+ at the lead site, and K or GA at the organic cation, CH₃NH₃, at A-site in cubic crystal. The simultaneous addition of Cu2+ and K to the perovskite crystal suppressed the crystal decomposition while inhibiting desorption of MA, improving the stability of the performance.